1999
DOI: 10.1046/j.1442-9993.1999.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource use and foraging patterns of honeybees, Apis mellifera, and native insects on flowers of Eucalyptus costata

Abstract: Introduced honeybees have become well established throughout Australia and concerns have been raised about their impact on the native flora and fauna. Such concerns include the possible depletion of nectar resources by honeybees to the detriment of native animals and the ability of honeybees to pollinate Australian plants. The foraging patterns and resource utilization of honeybees (Apis mellifera) and native insects on flowers of yellow Mallee (Eucalyptus costata) (Behr & F. Muell, ex F. Muell.) were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 9 publications
3
38
0
Order By: Relevance
“…Even though there was no statistically significant difference on the visit duration for each group, there was a slight trend of differentiation, probably because of the different bee body sizes. An increase in the number of honey bees in an area has been proven to depress the availability of nectar and pollen (Wills, Lyons & Bell, 1990;Horskins & Turner, 1999). This may explain why different sized wild bees react to this pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though there was no statistically significant difference on the visit duration for each group, there was a slight trend of differentiation, probably because of the different bee body sizes. An increase in the number of honey bees in an area has been proven to depress the availability of nectar and pollen (Wills, Lyons & Bell, 1990;Horskins & Turner, 1999). This may explain why different sized wild bees react to this pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently the fecundity, abundance, and ultimately survival of the wild bees are thought to be affected. Some authors have shown a negative impact of honey bees on native bee foraging, reproduction, and populations (Pyke & Balzer, 1985;Sugden, Thorp & Buchmann, 1996;Kato et al, 1999;Goulson & Sparrow, 2009); whereas other researchers did not find such impacts (Butz Huryn, 1997;Horskins & Turner, 1999;Roubik & Wolda, 2001;Paini, Williams & Roberts, 2005). The various and contrasting results among the studies, or in some cases even among areas/seasons from the same study, may arise from multiple factors that may affect the relationship between honey bees and wild bees (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of bees in the area also suggested that pollen could be carried several kilometres and be exchanged in the hive (B. Vaissiere, personal communication). Microsatellite markers helped to demonstrate that long-distance pollen-flow within populations is relatively common for wind-pollinated species (Dow and Ashley 1996;Streiff et al 1999) and insectpollinated species (Chase et al 1996;Horskins and Turner 1999;Konuma et al 2000).…”
Section: Reproductive Behaviour Inside the Seed Orchardmentioning
confidence: 99%
“…A search of ecological journals from 1993 to 2004 nevertheless found 61 papers reporting evidence of such facilitation across a range of habitats (7). Mechanisms by which invasive species can directly benefit native populations (7) include trophic subsidy, i.e., serving as a food source or providing limiting nutrients to higher trophic levels (8,9), modification or creation of habitat exploited by native species (10), and pollination of native plants (11,12). Invasive species may indirectly benefit native ones by ameliorating predation or competition (7), or through plant stress-mediated interactions, e.g., increased colonization of defoliated oaks by wood borers after gypsy moth, Lymantria dispar (L.), outbreaks (13).…”
mentioning
confidence: 99%